Impact of marathon performance on muscles stiffness in runners over 50 years old - Mackala, Krzysztof; Mroczek, Dariusz; Chmura, Paweł; Konefał, Marek; Pawlik, Damian; Ochman, Bartosz; Chmura, Jan; Paleczny, Bartłomiej; Seredyński, Rafał; Wyciszkiewicz, Małgorzata; Nowicka-Czudak, Adrianna; Łopusiewicz, Wojciech; et al. (Frontiers in Psychology, 2023)
This research examines the relationship between marathon performance and muscle stiffness changes from pre to marathon in recreational runners aged 50+ years. Thirty-one male long-distance runners aged 50–73 years participated in the experiment. The muscle stiffness of quadriceps and calves was measured in two independent sessions: the day before the marathon and 30 min after the completed marathon run using a Myoton device. The 42.195-km run was completed in 4.30,05 h ± 35.12 min, which indicates an intensity of 79.3% ± 7.1% of HRmax. The long-term, low-intensity running exercise (marathon) in older recreational runners and the low level of HRmax and VO2max showed no statistically significant changes in muscle stiffness (quadriceps and calves). There was reduced muscle stiffness, but only in the triceps of the calf in the dominant (left) leg. Moreover, to optimally evaluate the marathon and adequately prepare for the performance training program, we need to consider the direct and indirect analyses of the running economy, running technique, and HRmax and VO2max variables. These variables significantly affect marathon exercise